Pengetahuan Wanita Usia Subur (WUS) dalam Melakukan Deteksi Dini Kanker Serviks Metode Inspeksi Visualasam Asetat (IVA) - Romy Suwahyu; Nurul Septiani; Tomy Suganda; Kholis Khoirul Huda (SEHATI: Jurnal Kesehatan, 2024)
Cervical cancer is still a frightening thing for women and is the second deadliest cancer after breast cancer in Indonesia. The high incidence of cervical cancer in Indonesia is influenced by low screening coverage. Until 2021, only 6.83% of women aged 30–50 years had undergone screening examinations using the IVA method. This study aims to determine the level of knowledge of Women of Childbearing Age (WUS) in carrying out early detection of cervical cancer using the Acetic Acid Visual Inspection (IVA) method. This research applies an analytical survey design with a cross-sectional design, with a sample of 86 WUS selected using accidental sampling technique. Data were collected using a questionnaire, the data obtained was then analyzed using the Chi square test. The analysis results show that the p value = 0.00. It could be concluded that there is a relationship between the level of knowledge of Women of Childbearing Age (WUS) in carrying out early detection of cervical cancer using the Acetic Acid Visual Inspection (IVA) method.